The civic role of cultural spaces in culture and immigration : Reflections from the Becoming […] projects - Krasteva, Lora (Culture Caleidoscoop, 2022)
In this contribution I reflect on Becoming Czech, Romanian, Alman, and British – a series of creative residencies interrogating national identities and processes of belonging from the perspective of local first-generation immigrant artists and communities. I draw upon my lived experience and my advocacy as one of the co-founders of the UK-based Migrants in Theatre Movement to reflect upon the role of cultural spaces as sites of power and social change for and by immigrants.